Inventory Analysis of Rice Seed Materials at the UPTD Balai Benih Pertanian Kabupaten Bantul - Raichan Achwan Ramadani; Amelia Murtisari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
This study aims to analyze the inventory management of rice seed raw materials at UPTD Balai Benih Pertanian KabupatenBantul using the Economic Order Quantity (EOQ) method. The problem addressed in this study is the suboptimal control of raw material inventory, indicated by fluctuations in stock availability and the occurrence of stockouts in certain periods, which potentially disrupt the production process and increase inventory costs.The research method used is a quantitative descriptive approach with analysis techniques including EOQ, Safety Stock, and Reorder Point (ROP). The data used consist of primary and secondary data, including demand quantity, ordering costs, and holding costs during 2024.The results show that the optimal order quantity based on the EOQ method is 6,827.18 kg per order. The application of the EOQ method is also able to reduce the frequency of ordering and optimize total inventory costs. In addition, the calculation of Safety Stock and Reorder Point helps the company determine appropriate inventory reserves and reorder timing to avoid stock shortages.Thus, the implementation of the EOQ method can improve the efficiency of raw material inventory management for rice seeds, maintain the continuity of the production process, and minimize inventory costs at UPTD Balai Benih PertanianKabupaten Bantul.Keywords : Inventory, EOQ, Safety Stock, Reorder Point, Rice Seeds